The ghosts of the avant-garde(s) : exorcising experimental theater and performance - Harding, James Martin, 1958- (University of Michigan Press, 2013)
Pronouncements such as "the avant-garde is dead," argues the author, have suggested a unified history or theory of the avant-garde. This book examines the diversity and plurality of avant-garde gestures and expressions to suggest "avant-garde pluralities" and how an appreciation of these pluralities enables a more dynamic and increasingly global understanding of vanguardism in the performing arts. In pursuing this goal, the book not only surveys a wide variety of canonical and noncanonical examples of avant-garde performance, but also develops a range of theoretical paradigms that defend the haunting cultural and political significance of avant-garde expressions beyond what critics have presumed to be the death of the avant-garde. This book offers a striking perspective not only on key controversies and debates within avant-garde studies, but also on contemporary forms of avant-garde expression within a global political economy. --